2006
DOI: 10.1159/000094933
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the <i>BDNF</i> Gene in Autopsy-Confirmed Alzheimer’s Disease and Dementia with Lewy Bodies in Japan

Abstract: Background/Aim: Brain-derived neurotrophic factor (BDNF) is associated with the hippocampus and the nigrostriatal dopaminergic function. Data showing that its level was reduced in Alzheimer’s disease (AD) and Parkinson’s disease (PD) suggested that the BDNF function must play an important role in the pathogenetics of these diseases. Indeed, variation in the BDNF gene may confer susceptibility to AD and PD development. Recently, a functional BDNF Val66Met polymorphism has been found to be associated with episod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 85 publications
(58 reference statements)
0
37
0
Order By: Relevance
“…Previous studies have reported five positive results (12-16) and 21 negative results (19,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) between the BDNF Val66Met polymorphism and AD. In the present meta-analysis, no significant association was found between BDNF Val66Met and AD (P>0.05, Table II).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported five positive results (12-16) and 21 negative results (19,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) between the BDNF Val66Met polymorphism and AD. In the present meta-analysis, no significant association was found between BDNF Val66Met and AD (P>0.05, Table II).…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous carriers of the T-allele tend to have a higher risk of developing AD than non-carriers (36). There have been a total of four significant results (13,(17)(18)(19)) and 14 non-significant results (28)(29)(30)(31)(34)(35)(36)(37)40,41,(43)(44)(45) among the previous association studies between the BDNF C270T polymorphism and AD. In the present meta-analysis, the BDNF C270T polymorphism was found to increase the risk of AD by 88% in Asians under the dominant model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymorphism of the BDNF has been implicated with higher risk for AD. Especially for non-ApoE4 carriers and specific ethnic groups, this effect is well documented (100,101). A very interesting link is the fact that during aging and in AD, tau pathology starts in the entorhinal cortex and proceeds along the retrograde transport pathways of BDNF to the subiculum and CA1 subfield and then to the basal forebrain, amygdale and finally to several cortical regions (90).…”
Section: Neuroplasticity Hypothesis Of Alzheimer's Diseasementioning
confidence: 99%
“…Detailed characteristics of all eligible studies included in meta-analysis are reported in Table 1. One overall study was conducted on BDNF 196GA polymorphism and 3 ethnicity specific studies were conducted, that includes 8 studies on American populations [30][31][32][33][34][35][36], 11 studies on Asian populations [37][38][39][40][41][42][43][44][45][46][47] and 12 studies on European populations [35,[48][49][50][51][52][53][54][55][56][57][58]. Moreover, one overall study was also conducted on BDNF 270CT polymorphism and 3 ethnicity specific studies were also possible, that includes 5 studies on American populations [30,31,33,34,59], 7 studies on Asian populations [37,39,41,42,44,46,60] and 7 studies on European populations [48,49,52,…”
Section: Eligible Studies Included In the Meta-analysismentioning
confidence: 99%